2022
DOI: 10.1016/j.jcrc.2021.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of outcome and characteristics between 6343 COVID-19 patients and 2256 other community-acquired viral pneumonia patients admitted to Dutch ICUs

Abstract: Purpose Describe the differences in characteristics and outcomes between COVID-19 and other viral pneumonia patients admitted to Dutch ICUs. Materials and methods Data from the National-Intensive-Care-Evaluation-registry of COVID-19 patients admitted between February 15th and January 1th 2021 and other viral pneumonia patients admitted between January 1st 2017 and January 1st 2020 were used. Patients' characteristics, the unadjusted, and adjusted in-hospital mortality w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…This was calculated as the number of occupied beds at the day of ICU admission at the pertinent ICU as percentage of the daily average in 2019 specific for that ICU. 19,20 T To better understand the differences in characteristics between the different cohorts and their effect on outcome, case-mix adjustments were performed in steps.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This was calculated as the number of occupied beds at the day of ICU admission at the pertinent ICU as percentage of the daily average in 2019 specific for that ICU. 19,20 T To better understand the differences in characteristics between the different cohorts and their effect on outcome, case-mix adjustments were performed in steps.…”
Section: Discussionmentioning
confidence: 99%
“…Brinkman and colleagues previously analyzed the differences in characteristics and outcomes of COVID-19 patients of all ages compared to patients with other viral pneumonia admitted in a historical time period and demonstrated a prolonged hospital LOS and a significantly higher inhospital mortality rate for the patients with COVID-19. 20 We exclusively included patients ≥70 years old and additionally compared with patients admitted in the same time period. The study of Guidet and colleagues, demonstrated an increased 30-day mortality in patients ≥80 years old admitted to the ICU with COVID-19, compared to patients with respiratory failure without COVID-19.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most patients with COVID-19 are asymptomatic or paucisymptomatic initially, but some of them develop both progressive respiratory failure and multiple organ failure 10 , 11 . The mortality rate of COVID-19 is higher than for other viral pneumonias 12 . Although the details are unclear, the increased thrombosis associated with COVID-19 may contribute to its high mortality 13 .…”
Section: Introductionmentioning
confidence: 78%
“…Another limitation to mention is the fact that we only included patients discharged from the hospital to the home, which may not be representative of the whole population of ICU patients in this period. Almost one-third of COVID-19 patients admitted to Dutch ICUs died in the hospital [ 57 ]. The majority of the ICU patients admitted during this study period were transferred to a rehabilitation center or nursing home and received a structured rehabilitation care plan.…”
Section: Discussionmentioning
confidence: 99%